Some Validation Tests of the OTM, ver. 5.0 - Vuk, Goran; Hansen, Christian Overgård (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
The tactical traffic model for greater Copenhagen, the OTM model, was updated to its 5th version in a 21⁄2-year long project lasting from January 2005 till April 2007. The model was updated especially for the purpose of the Metro City Ring project (approved in the Danish Parliament in June 2007). The biggest part of the efforts were placed on the data part of the model, where especially new base 2004 travel matrices were built. Apart from that, the model was completely re-estimated, starting from new values-of-time (VOTs), based on the newly completed data for the Danish national VOT project, and ending with the newly developed pivot-point procedure. Finally, the model zoning system, plan data and road/public transport networks were updated to reflect the new model base year of 2004. The clients in the project were the Danish Ministry of Energy and Transport, the Danish Ministry for Financing, the Copenhagen and Frederiksberg municipalities, the Railway and Road Directories, and the Greater Copenhagen Authority. The project was completed by the Danish Transport Research Institute (DTF, DTU), the Centre for Transport and Traffic (CTT, DTU), TetraPlan, RAND Europe, COH ApS and COWI. The aim of the paper is twofold. Firstly, we depict the structure of the new OTM demand model (chapter 2). Secondly, we present base year validations, sensitivity tests, and results from a back casting experiment (chapter 3 and 4). Conclusions are listed in the last section of the paper (chapter 5).